Congenital Tuberculosis: A New Concern in the Neonatal Intensive Care Unit. (October 2018) - Newberry, Desi M.; Robertson Bell, Tracey
Abstract : Background: Congenital tuberculosis (TB) is rare in the United States. Recent immigration patterns to the United States have made the diagnosis of congenital TB an important public health issue. Purpose: To explore the epidemiology, pathophysiology, diagnostic evaluation, treatment, and prognosis for congenital TB. The implications for exposed healthcare professionals in the neonatal intensive care unit (NICU) setting are also explored. Methods/Search Strategy: Relevant articles were accessed via PubMed, CINAHL, and Google Scholar. Findings/Results: Until 1994, fewer than 400 cases of confirmed congenital TB had been reported in the literature worldwide. An additional 18 cases were reported from 2001 to 2005. Neonatal providers need to be aware of the potential for congenital TB infection as the immigrant population in the United States continues to increase, many of whom originate from TB endemic countries. Implications for Practice: The interpretation of TB-specific tests is problematic in newborns due to decreased sensitivity and specificity. Congenital TB should be ruled out in infants with signs and symptoms of sepsis or pneumonia and in whom broad-spectrum antibiotic therapy does not improve their clinical status. Implications for Research: The interpretation of TB-specific tests is problematic in newborns due to decreased sensitivity and specificity; more research is needed regarding best practice in diagnosis. Established protocols are needed to address the healthcare of TB-exposed providers in the NICU.